Pre-service English Teachers’ Perceptions on Their Professional Identity through LinkedIn-Mediated Activities - Astri Hapsari; Diah Agustina Ratu; Muhammad Mukhlas; Resnia Novitasari (VELES Voices of English Language Education Society, 2022)
In English as a Foreign Language (EFL) context, pre-service English teachers need to develop their sense of identity in both real communities in society and online platforms.This study aims to analyse pre-service English teachers’ views on their engagement in LinkedIn-mediated early professional development activities . The data were collected through in-depth interviews. Three pre-service English teachers who enrolled in Teacher Professional Development coursework and engaged in LinkedIn-mediated activities during the coursework were invited to participate. Two themes emerged from the findings. The first is LinkedIn-mediated early professional development activities that raise awareness on developing current professional digital footprint. The second is  LinkedIn-mediated early professional development activities help them to figure out expected teacher-selves in the future. Implications for future pedagogical practicein the Teacher Professional Development coursework is that the activities involved in LinkedIn should be sustained and enhanced in order to support the pre-service English teachers to shape their professional identity as future English teachers.